Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsabm.1c00513
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ToF-SIMS Analysis of Macrophage Content from a Human Cranial Triphasic Calcium Phosphate Implant

Abstract: Macrophages play a key role in determining the fate of implanted biomaterials, especially for biomaterials such as calcium phosphates (CaPs) where these cells play a vital role in material resorption and osteogenesis, as shown in different models, including clinical samples. Although substantial consideration is given to the design and validation of different CaPs, relatively little is known about their material–cell interaction. Specifically, the intracellular content of different CaP phases remains to be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Even though pyrophosphate is known as a key regulator in biomineralization in vivo , inhibiting spontaneous mineralization, acting as the body's own softener and being part of normal metabolism (Fleisch & Bisaz, 1962 ; Millán, 2013 ; Orriss et al., 2016 ), we hypothesize that the complex crosstalk and feedback loops involved with pyrophosphate in the process of biomineralization could be central to the mechanism of which our CaP material is recognized and replaced by bone. This is supported by the presence of pyrophosphate intracellularly in macrophages exposed to the same CaP material surrounded by newly formed/mature bone, which was one of the key findings from a clinical implant explanted after 31 months due to tumor recurrence (Malmberg et al., 2021 ). Furthermore, exclusion of the pyrophosphate seems to evoked premature resorption of monetite and β‐TCP of a similar CaP material in large animal studies (Kihlström Burenstam Linder et al., 2019 ), highlighting the potential promoting role of pyrophosphate in biomineralization (Le Gars Santoni et al., 2022 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Even though pyrophosphate is known as a key regulator in biomineralization in vivo , inhibiting spontaneous mineralization, acting as the body's own softener and being part of normal metabolism (Fleisch & Bisaz, 1962 ; Millán, 2013 ; Orriss et al., 2016 ), we hypothesize that the complex crosstalk and feedback loops involved with pyrophosphate in the process of biomineralization could be central to the mechanism of which our CaP material is recognized and replaced by bone. This is supported by the presence of pyrophosphate intracellularly in macrophages exposed to the same CaP material surrounded by newly formed/mature bone, which was one of the key findings from a clinical implant explanted after 31 months due to tumor recurrence (Malmberg et al., 2021 ). Furthermore, exclusion of the pyrophosphate seems to evoked premature resorption of monetite and β‐TCP of a similar CaP material in large animal studies (Kihlström Burenstam Linder et al., 2019 ), highlighting the potential promoting role of pyrophosphate in biomineralization (Le Gars Santoni et al., 2022 ).…”
Section: Discussionmentioning
confidence: 85%
“…The interplay between macrophages and osteoblasts is crucial for bone formation and the macrophage response dictates the fate of implanted biomaterials (Chang et al, 2008;Loi et al, 2016;Miron & Bosshardt, 2016;Pajarinen et al, 2019;Sridharan et al, 2015;Vasconcelos et al, 2019), which was demonstrated in a previous study (Chang et al, 2008), where the depletion of osteal macrophages inhibited osteoblast differentiation and mineralization. Other studies investigating same CaP composition in non-load bearing applications show macrophages as the main cells after few weeks, months and years of implantation in vivo models (Gallinetti et al, 2021;Malmberg et al, 2021). However, these studies investigate bone formation in calvarial defect models rather than the herein used calvarial model for vertical bone augmentation.…”
Section: Discussionmentioning
confidence: 93%
“…The CaP composition studied here has been shown to have a higher healing capacity in craniomaxillofacial reconstruction where it has been shown to be resorbed and replaced by bone during the healing process both in preclinical and clinical settings without signs of chronic inflammation [19,20,46,48,[67][68][69][70]. This response seems to be clearly coupled with the material-macrophage interaction over time [19,20,46,47]. Taken together we, therefore, propose that both the complement and contact system activating properties of this CaP with blood at implantation initiate both the activation and recruitment of leukocytes and osteoblasts and inhibit osteoclasts at the site of implantation.…”
Section: Discussionmentioning
confidence: 83%
“…A considerable presence of osteoblasts has been observed at early and late stages in preclinical models. Interestingly, minimal osteoclast activity was observed [19,20,[46][47][48]; instead, a moderate to substantial presence of material-filled macrophages was observed, which are also responsive to the complement proteins C3a, C5a, and bradykinin [49]. Contrarily, titanium meshes [19], solid titanium implants, and PEEK have been found to trigger a foreign body reaction, leading to chronic inflammation that promotes fibrous encapsulation rather than bone formation [19,25,50].…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of biomaterials in vivo is also a research focus of ToF-SIMS ( Eriksson et al, 2008 ; De Carvalho et al, 2020 ; Kruppke et al, 2020 ; Malmberg et al, 2021 ). Implant healing into bone tissue, which involves the growth and fusion of mature bone with the implant, has also been studied using ToF-SIMS imaging.…”
Section: Bioimaging Applications In Tof-simsmentioning
confidence: 99%